2021
DOI: 10.1002/cl2.1148
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: What are the effects of different elements of media on radicalization outcomes? A systematic review

Abstract: Objectives In this systematic review and meta analysis we will collate and synthesize the evidence on media‐effects for radicalization, focusing on both cognitive and behavioral outcomes. The goal is to identify the relative magnitudes of the effects for different mediums, types of content, and elements of human‐media relationships. Methodology Random‐effects meta analysis will be used and the results will be rank‐ordered according to the size of the pooled estimates for the different factors. Meta‐regressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…It is also of note that whilst only small, there are statistically significant differences in the effects for both general media usage (for cognitive radicalization) and radical content consumption (for behavioral radicalization) between regions, with the effects for both factors being larger for European studies. Previous research has found that only a small number of risk factors for radicalization display regional heterogeneity (Wolfowicz, Hasisi, et al, 2021). Future research may find benefit in examining the issue from a cultural perspective, which may consider how different cultures relate to media usage more generally or use media differently.…”
Section: Authors' Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also of note that whilst only small, there are statistically significant differences in the effects for both general media usage (for cognitive radicalization) and radical content consumption (for behavioral radicalization) between regions, with the effects for both factors being larger for European studies. Previous research has found that only a small number of risk factors for radicalization display regional heterogeneity (Wolfowicz, Hasisi, et al, 2021). Future research may find benefit in examining the issue from a cultural perspective, which may consider how different cultures relate to media usage more generally or use media differently.…”
Section: Authors' Conclusionmentioning
confidence: 98%
“…This is the type of research that may serve to improve the effectiveness of online surveillance technologies and prevention efforts more generally. Unfortunately, to date, there are a very limited number of studies that have taken this approach (e.g., Scrivens et al, 2021; Wolfowicz, Hasisi, et al, 2021).…”
Section: Authors' Conclusionmentioning
confidence: 99%
“…Most notable is our programme of reviews on countering violent extremism, brokered by the Co‐chair of our Crime & Justice Group, Peter Neyroud, and funded by the US Department of Homeland Security and Public Safety Canada. This programme has published four reviews to date—for example, Carthy et al (2020) and Mazerolle et al (2021)—with another nine ongoing—including Zych and Nasaescu (2021) and Wolfowicz et al (2021).…”
mentioning
confidence: 99%